Normative and subjective need for dental prosthesis: accuracy and agreement in a population based-study - Luiz Alexandre Chisini; Hugo Ramalho Sarmento; Bernardo Lessa Horta; Flávio Fernando Demarco; Marcos Britto Correa (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2021)
Abstract: The aim of our study was to compare normative need for dental prosthesis (estimated by dentists) with subjective need (self-reported) by testing the accuracy and agreement and comparing direction and magnitude of associations with independent variables using both as outcomes. A representative sample of a birth cohort study (n = 900) was assessed at 31 years of age. Subjective need was obtained from questionnaire. Both normative and subjective need variables were dichotomized in (a) individuals with need for dental prosthesis and (b) without need for dental prosthesis. Accuracy was assessed by sensitivity (SE), specificity (SP), positive (PPV) and negative (NPV) predictive values. Agreement of normative and subjective need was assessed estimating kappa index. Sex, income, educational level, use of dental services and self-reported oral health were used to compare the associations with normative and subjective need. Prevalence of normative need was 48.9% and subjective need was 34.9%. Agreement (kappa: 0.43) and accuracy between normative and subjective need for dental prosthesis was low (SE: 56.5, 95%CI: 50.3-62.6; SP: 85.8, 95%CI: 81.1-89.7; PPV: 79.1, 95%CI: 72.6-84.7; NPV: 67.3, 95%CI: 62.1-72.2). When considering individuals with loss in anterior teeth, results showed a good agreement (kappa: 0.82) and accuracy between normative and subjective need (SE: 93.3, 95%CI: 68.1-99.8; SP: 88.9, 95%CI: 51.8-99.7; PPV: 93.3, 95%CI: 68.1-99.8; NPV: 88.9, 95%CI: 51.8-99.7). Direction and magnitude of associations with normative and subjective need were similar. Thus, normative need for dental prosthesis differs from subjective need in adults, except when anterior losses are present.